The Dynamics of Stakeholder Participation in Marine Protected Area Development - Oracion, Enrique G. (Silliman Journal, 2022)
This case study examines the dynamics of stakeholder participation in the establishment, management, and sustainability of the marine sanctuaries in Balayan Bay covering the municipalities of Mabini and Tingloy in Batangas, Philippines. The study interviewed purposive samples of individuals who use Balayan Bay and who are therefore either directly or indirectly involved in or impacted by the establishment of the marine sanctuaries. For comparative analysis, the stakeholders are identified as locals, indirect brokers, direct brokers, and tourists. The result of the study showed that the extent of participation of the locals reflects the limited benefits they have derived fi-om the marine sanctuaries, their perceived loss of control over the management of these marine sanctuaries, and their growing sense of alienation from them as a consequence of the takeover by the tourism sector. This paper argues that the identification of all stakeholders must be an ongoing process to cover all who have interest over the same marine space, including those who may not have been originally involved in 'the establishment of the marine sanctuaries. The participation of these stakeholders in the management should be encouraged and sustained through the equitable distribution of benefits in various forms. Among other recommendations, this study supports the pursuance of the plan for a common resource management program for the bay being the shared fishing ground and a tourist destination of the two municipalities.